The Historical Roots of the Global Testing Culture in Education (Foro de Educacion, 2019)
This article takes as its starting point the idea that contemporary education is characterised by the presence of a global testing culture. The global testing culture reflects the fact that students’ learning outcomes and learning standards are at the centre of policymakers’ attention all over the world. Thus, the global testing culture plays a significant role in both educational policies and the conditions under which education is practiced in different national contexts. The aim of the article is to offer a brief, select outline of the precursors, antecedents, and preconditions that have promoted and facilitated the rise of our modern day global testing culture. The article is structured according to two chronological stages. The first stage encompasses a confluence of comparative education, the rise of applied psychology, and the transnational organisational structures that began forming in the pre-WWII setting. The second stage features the emergence of the foundations and organisations of the global testing culture in the wake of WWII, a period pre-occupied with educational measurement and comparisons. The article argues that these developments, which built on a framework established mainly during the interwar years, subsequently conflated into a trajectory that was fostered and promoted by policies during the Cold War, and became dominant from the 1990s onwards.